STRATEGI MENINGKATKAN TINGKAT HUNIAN KAMAR PADA HOMESTAY DI DESA WISATA RAYA KECAMATAN BERASTAGI KABUPATEN KARO - Muhammad Hamdani (Jurnal Ilmiah Akomodasi Agung, 2023)
This study aims to reveal and analyze effective strategies in increasing room occupancy rates in homestays located in Raya Tourism Village, Berastagi District, Karo Regency. This village has great potential in the tourism industry, but the occupancy rate of homestay rooms has not reached its maximum potential. Therefore, this study adopted a qualitative approach by collecting data through in-depth interviews, observation, and document analysis. The results of this study reveal that there are several strategies that can increase room occupancy rates in homestays in Raya Tourism Village. First, environmental sustainability must be improved, including waste management, natural resources, and environmental hygiene. Second, more intensive and targeted promotion is needed to increase tourists' awareness of homestays in Desa Wisata Raya. Third, quality service and personalization of the guest experience can be key factors in retaining and attracting return tourists. Fourth, collaboration between homestay owners, local government, and other relevant parties can strengthen the tourism infrastructure in the village. In this context, this study provides an in-depth insight into the strategies that can be applied to increase room occupancy rates at homestays in Desa Wisata Raya. These results can be a valuable guide for homestay owners, local government, and other stakeholders in tourism development in the region. In addition, this study also contributes to the qualitative research literature in the context of tourism and tourist village development.